Studying the cerebral cortex electrical activity of individuals with different psychosocial type in a model of social behavior - Kotsan, Ihor Ya.; Fedorchuk, Oksana; Kuznietsov, Illia P.; Коцан, Ігор Ярославович; Федорчук, Оксана; Кузнєцов, Ілля Павлович (Східноєвропейський національний університет імені Лесі Українки, 2013)
During the experiment the main frequency EEG ranges were determine. Their activity is specific to a particular psychosocial type. Psychosocial type of probationers was determined by a complex psychological technique. According to the results all individuals were divided into two psychological groups: with selfish-authoritarian type of social behavior and with friendly-altruistic type. Based on the specific requirements for ERD- / ERS-researches we have created our own methodology – a game «mini-basketball». This model of social behavior has been adapted for selfish and altruistic types of individual social activity. Besides, for the results comparison with available in the literature data, another test situation – play «Stag hunt» was used. Experimental results suggest that the established model of social behavior clearly reflects the ways of it expression in the examined individuals. Analysis of the action choice results in the presented games coincides with different individual’s social orientation according to the survey.
Keywords: altruїzm; egoїzm; sinhronіzatsіya; desinhronіzatsіya